The Role of Artificial Intelligence Applications in Developing Children's Skills: The Language Skill as a Model (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The research aims to explore the role of smart applications in developing and enhancing educational skills during childhood and their impact on achieving a safe and prosperous childhood compared to traditional education systems, while also seeking to identify the activities of artificial smart applications in the educational field, their positive areas, and the obstacles they may encounter.  Recent studies have shown that investing in artificial intelligence in the field of education effectively contributes to the development of various skills in children, including language skills. Artificial intelligence is considered an innovative tool for improving teaching and learning methods during childhood, thereby enhancing and developing linguistic and intellectual skills. Fundamental knowledge of artificial intelligence helps children decode fundamental operations of daily technology like social media algorithms. The early introduction to artificial intelligence education enables students to understand complex subjects better while building a positive curiosity and growing confidence rather than developing fear or withdrawal or isolation habits.  The implementation of artificial intelligence technology in children's lives seeks to educate them about reduced versions of this technology which can both spark their curiosity and boost their creative abilities. The presentation Enhances their motivation for education. Teaching aids that use AI technology create interactive activities which enable students to approach AI systems through enjoyable educational experiences. The educational brain games for children serve a doubled purpose that improves their academic abilities together with developing mental capabilities crucial for growth.UNICEF recognizes early artificial intelligence education as critical for children because starting education at this time helps them acquire diverse developmental capabilities.  The graduates acquire analytical competence for assessing and evaluating information by developing their critical thinking abilities.  Student creative problem-solving abilities increase after developing problem-solving skills.  The process of creating new innovative ideas becomes more successful through students who employ creative cognitive abilities.  The development of ethical awareness skills happens by interaction with the technological world to understand its ethical dimensions of interaction.  Computers that connect directly to interpersonal dialogue enable students to develop language capabilities and expand their vocabulary alongside the improvement of their communication skills.  The time is appropriate to make artificial intelligence investments in education because children require necessary competencies to confront upcoming difficulties and seize future opportunities. Children must receive artificial intelligence education at an early age because it will shape their development as advanced technological users of the future. The denial of artificial intelligence access to children at present leads to an irreversible loss of advanced career potentials that will appear in their future lifetime.  Our present moment demands immediate implementation of the essential technological instrument which will serve our children in the future. Implementing artificial intelligence education for children at a young age creates possibilities for them to become future technology leaders by developing their innovative capabilities through this foundation.